O turismo rural de Goiás: contextos imaginários - Nogueira, Maria Francisca Magalhães (2009)
This thesis is a reflection on rural tourism in Goiás, which goes beyond the functional and economic approaches due to the belief that this sort of tourism is attached to a world of significations that exits as it is. This complex object of study is analyzed by two scopes of strategic movements. The first part describes the rural tourism as reality and rationality constituted and in the process of being constituted (in fien) and it was also reduced to some institutions and significations. The main preoccupation was to develop a context of terms and entities, elements and relations that would allow the rural tourism of Goiás to be conceived within its own structures, functions as well as its history and significations. The rural tourism of Goiás was treated as it is in reality of an institutionalized imaginary, focusing on the contextualization of the scenery in which the object is in the state of Goiás. The second part deals with the imaginary of the rural tourist, based on the social imaginary of Goiás , of which society , since XIX century up until now, was almost rural exclusively. In order to explore the imaginary of the rural tourist as a world of significations, an empirical research was carried out. Tourists from five different establishments of rural tourism situated in the region of Goiânia were interviewed. It was not our ambition to comprehend the whole universe of remits and significations of the imaginary of the tourist, but only to show some of their angles and facets, in a oblique way. For the tourists, the countryside has an imaginary signification, which makes them want to go there. The analysis of the rural tourism of Goiás: Imaginary contexts was made according to the complex thought of Edgar Morin and by categories developed by Corneliu Castoriadis. Based on the perception of the process in fieri of the investigated object, which is on continuously creation and transformation, considerations and conclusions were let open to the reader